A critical investigation into the managerial implications of inclusive education - Cloete, Sanet (Rhodes University, Faculty of Education, Department of Education, 2002)
Special needs education has always provided special challenges to school administrators, policy makers and teachers. The world-wide move towards inclusive education as an alternative to exclusive education or casual mainstreaming has resulted in significant developments in Namibia in the past decade. Global educational reforms have focused on education for all as well as inclusive education and Namibia is signatory to several conventions and declarations in this regard. Research in this field has largely focused on the role of the inclusive teacher, and of course the special needs of the learners. Little or no attention has been paid to possible managerial and organisational challenges which accompany the move to inclusive education. This thesis seeks to critically investigate the managerial implications of inclusive education. The focal point of this research is to gain a clear understanding of the managerial implications in an inclusive school for learners with visual impairment, chiefly through an exploration of the experiences of management members of the inclusive process. The research is located within a qualitative research paradigm, which is subsumed by a phenomenological model. The data gathered through in-depth interviews include many anecdotal accounts that provide insight into the ways respondents reacted to experiences at the inclusive school. The main findings of the research are highlighted and discussed. Recommendations arising from a critical analysis of these main findings are presented.
Keywords: School management and organization -- Namibia